Environmental Risk Factors for Lung Cancer Mortality in the Cancer Prevention Study-II - Turner, Michelle C (Université d'Ottawa / University of Ottawa, 2012)
This thesis examined associations between ecological indicators of residential radon and fine particulate matter air pollution (PM2.5) and lung cancer mortality using data from the American Cancer Society Cancer Prevention Study-II (CPS-II) prospective cohort. Nearly 1.2 million CPS-II participants were recruited in 1982. Mean county-level residential radon concentrations were linked to study participants according to ZIP code information at enrollment (mean (SD) = 53.5 (38.0) Bq/m3). Cox proportional hazards regression models were used to obtain adjusted hazard ratios (HRs) and 95% confidence intervals (CI) for lung cancer mortality associated with radon. After necessary exclusions, a total of 811,961 participants in 2,754 counties were retained for analysis. A significant positive linear trend was observed between categories of radon concentrations and lung cancer mortality (p = 0.02). A 15% (95% CI 1 - 31%) increase in the risk of lung cancer mortality was observed per each 100 Bq/m3 radon. Radon was also positively associated with chronic obstructive pulmonary disease mortality (HR per each 100 Bq/m3 = 1.13, 95% CI 1.05 - 1.21). No clear associations were observed between radon and non-respiratory mortality. In lifelong never smokers (n = 188,699), each 10 µg/m3 increase in mean metropolitan statistical area PM2.5 concentrations was associated with a 15-27% increase in the risk of lung cancer death which strengthened among individuals with a history of asthma or any prevalent chronic lung disease at enrollment (p for interaction < 0.05). There was no association between PM2.5 and mortality from non-malignant respiratory disease. In conclusion, this thesis observed significant positive associations between ecological indicators of residential radon and PM2.5 concentrations and lung cancer mortality. These findings further support efforts to reduce radon concentrations in homes to the lowest possible level and strengthens the evidence that ambient concentrations of PM2.5 measured in recent decades are associated with small but measurable increases in lung cancer mortality. Further research is needed to better understand possible complex inter-relationships between environmental risk factors, chronic lung disease, and lung cancer.
Keywords: radon; air pollution; lung cancer; COPD; cohort studies